The Third National Health and Morbidity Survey (NHMS III) 2006: nutritional status of adults aged 18 years and above - Mohammad Nor, Noor Safiza; Khor, Geok Lin; Shahar, Suzana; Kee, Chee Cheong; Haniff, Jamaiyah; Appannah, Geeta; Rasat, Rahmah; Wong, N. F.; Zainuddin, Ahmad Ali; Ab Rahman, Jamaluddin; Abd Talib, Ruzita; Yusoff, Ahmad Faudzi (Nutrition Society of Malaysia, 2008)
1Department of Nutrition Research, Institute for Public Health, Ministry of Health, Kuala Lumpur; 2Department of Nutrition and Dietetics, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 43400 Serdang, Selangor; 3Department of Nutrition and Dietetics, Faculty of Allied Health Sciences, Universiti Kebangsaan Malaysia, 50300 Kuala Lumpur; 4Epidemiology and Biostatistics Unit, Institute for Medical Research,Kuala Lumpur; 5Clinical Epidemiology Unit, Clinical Research Centre, Ministry of Health, Kuala Lumpur; 6Department of Paediatrics, Universiti Kebangsaan Malaysia, Kuala Lumpur; 7Department of Community Health and Family Medicine, Faculty of Medicine, International Islamic University, Kuantan The Third National Health and Morbidity Survey (NHMS III) was conducted in 2006 to determine the nutritional status of a nationally representative sample of Malaysian adults aged 18 years and above. Body weight, height and waist circumference measurements were taken by trained health nurses according to a standard procedure (WHO, 1998). Body Mass Index (BMI) was determined among 33,055 eligible adults, while risk of abdominal obesity based on waist circumference (WC) was obtained from 32,900 individuals. In addition, peripheral muscle wasting was determined using calf circumference (CC) among 4,282 older individuals aged 60 years and above. The national prevalence of normal BMI (BMI 18.5-24.9 kg/m2) was 48.4% (47.7–49.0)*. The prevalence of underweight (BMI <18.5 kg/m2) was 8.5% (8.2–8.9), being higher in rural areas {9.8% (9.2–10.4)} than in urban areas {7.8% (7.4–8.3)}. Meanwhile, 29.1% (28.6–29.7) of the adults were overweight (BMI 25.0-29.9 kg/m2). Among the ethnic groups, Indians had the highest prevalence of overweight followed by Malays and Chinese. In addition, 14.0% (13.6–14.5) of the adults were obese (BMI >30.0 kg/m2). Women had higher obesity prevalence at 17.4% (16.7–18.0) than men at 10.0% (9.5–10.5). In terms of ethnic groups, Indians and Malays had higher obesity prevalence than other groups. By occupation category, housewives showed the highest prevalence of obesity at 20.3% (19.4–21.3). The prevalence of abdominal obesity (WC for women >88 cm and men >102 cm) was 17.4% (16.9-17.9), with women showing higher prevalence {26.0% (25.2-26.8)} than men {7.3% (6.7-7.6}. The prevalence of older persons with peripheral muscle wasting (calf circumference for women < 27.3 cm and men < 30.1 cm) was 19.9% (18.5–21.6), with a higher prevalence of men {23.7% (21.6-25.9)} than women {16.8% (15.1-18.5)} at risk of malnutrition according to this indicator. In comparison, the present national prevalence of underweight of 8.5% was three times lower than that (25.2%) reported in the NHMS II in 1996. In contrast, the prevalence of overweight hasof 14.0% in this study and 12.7% in the MANS were approximately three times the level of 4.4% found in 1996 (NHMS III). This alarming trend calls for serious re-examination of public health programmes for more effective reduction of obesity among Malaysian adults. increased from 16.6% in the NMHS II to 29.1% in the present study. The latter is comparable with the finding of 27.4% reported in another nationally representative sample involving over 5,000 adults namely, the Malaysian Adults Nutrition Survey (MANS) conducted in 2003. It is noted that obesity prevalence of 14.0% in this study and 12.7% in the MANS were approximately three times the level of 4.4% found in 1996 (NHMS III). This alarming trend calls for serious re-examination of public health programmes for more effective reduction of obesity among Malaysian adults.